Information encryption algorithm based on two chaotic dynamic systems for secure communication systems - Косован, Григорій Васильович; Кушнір, Микола Ярославович; Політанський, Леонід Францович (Ukrainian Information Security Research Journal, 2013)
At the present stage of development of information technology, telecommunication equipment and computer equipment commonly raises the problem of protecting confidential information against unauthorized access when it is transmitting or storing. To solve this problem often turn to cryptographic methods of information security. In addition to encryption methods based on algebraic concepts, conducted the development of algorithms based on deterministic chaos. In this paper presents an algorithm encrypt text data, based on the use of two dynamical systems, systems Roessler and cubic map. Ressler system used for generation of the initial conditions used cubic map when encrypting each character of message. As a result of this algorithm plaintext symbols incoming messages by encrypting replaced by integers. The work was also carried out modeling of dynamic systems in Matlab environment and given an example an example of the application written in Delphi 7. In this paper also assessed the security of the proposed algorithm. The algorithm has a large number of encryption keys, that making the process of their selection is very difficult. Using two dynamic systems complicates the possibility of statistical attacks.